Shape-sensing robotic-assisted bronchoscopy combined with cone-beam computed tomography-guided cryoablation for malignant lung tumors - Zhang, Chunxi; Xie, Fangfang; Xi, Houteng; Liu, Shuaiyang; Yan, Lijun; Wang, Zhexin; Yao, Feng; Herth, Felix; Sun, Jiayuan (Respiration, 2025)
Introduction: For malignant lung tumor patients who are poor surgical candidates, transbronchial cryoablation is a promising alternative treatment method and is safer than percutaneous cryoablation. This case report presents the initial clinical experience of shape-sensing robotic-assisted bronchoscopy (ssRAB) combined with cone-beam computed tomography (CBCT)-guided cryoablation for malignant lung tumor patients. Case Presentation: Transbronchial cryoablation was performed in 6 patients. Three patients diagnosed with pulmonary adenocarcinoma underwent ssRAB combined with CBCT-guided cryoablation for local tumor treatment. Two patients with lesions suspected to be malignancy underwent transbronchial diagnosis and cryoablation under the guidance of ssRAB and CBCT in one procedure. One patient with two lesions suspected to be malignancy underwent ssRAB combined with CBCT-guided cryoablation for one lesion, accompanied by transbronchial localization followed by wedge resection for another lesion in one procedure. In all 6 patients, transbronchial cryoablation was successfully performed, with the ablation zones fully covering the target lesions. No procedure-related complications occurred. Conclusion: ssRAB combined with CBCT-guided cryoablation is feasible for malignant lung tumor patients.